2021
DOI: 10.21608/eajbsf.2021.146336
|View full text |Cite
|
Sign up to set email alerts
|

The Insecticidal Activity of Artemisia absinthium leaves Extracts Against Blowfly,Chrysomya albiceps (Calliphoridae)

Abstract: http://eajbsf.journals.ekb.eg/ The Insecticidal Activity of Artemisia absinthium leaves Extracts Against Blowfly,Chrysomya albiceps (Calliphoridae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…However, the present study showed that the highest mortalities were recorded in the petroleum ether extract of J. procera stem with LC 50 0.15 g/mL. The petroleum ether leaves extract of Artemisia absinthium at 0.4 g/mL caused 100% larval mortality on C. albiceps with LC 50 of 0.11 g/mL [21] . Therefore, the test methods, differences between species, and exposure time to the test materials may be responsible for the differences among the obtained results.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…However, the present study showed that the highest mortalities were recorded in the petroleum ether extract of J. procera stem with LC 50 0.15 g/mL. The petroleum ether leaves extract of Artemisia absinthium at 0.4 g/mL caused 100% larval mortality on C. albiceps with LC 50 of 0.11 g/mL [21] . Therefore, the test methods, differences between species, and exposure time to the test materials may be responsible for the differences among the obtained results.…”
Section: Discussioncontrasting
confidence: 49%
“…The reproductive efficiency of females resulting from the treated larval was carried out according to Alhuraysi et al [21] . The females that successfully emerge from treated larvae were picked up and transferred with normal adult males (untreated) to the wooden cages (25×25×25 cm).…”
Section: Reproductive Potential Of Resulting Femalesmentioning
confidence: 99%
See 3 more Smart Citations